How does eco-driving make us feel? Considering the psychological effects of eco-driving. (May 2022) - Allison, Craig K.; Stanton, Neville A.; Fleming, James M.; Yan, Xingda; Lot, Roberto
Abstract: Despite both the environmental and financial benefits of eco-driving being well known, the psychological impact of engaging in eco-driving behaviours has received less attention within the literature. It was anticipated that being asked to engage in eco-driving behaviours not only has an impact on vehicle fuel usage, but also on the driver, both in terms of their overall mood and willingness to re-engage with the task at a later time. Results from a simulated driving study suggest that although eco-driving was beneficial in reducing fuel consumption, being asked to eco-drive had a negative effect on overall journey time and mood. Engaging in eco-driving did however have a positive effect on self-esteem, suggesting potential longer term psychological benefits of adopting this behaviour. Highlights: A repeated measures study demonstrated participants significantly reduced fuel usage by engaging with eco-driving. Despite reducing fuel usage, engaging with eco-driving techniques had largely negative psychological effects on drivers, based on self-report data. Participants' self-esteem was increased after engaging with eco-driving, suggesting potential psychological as well as environmental benefit.